RED BEAN (PHASEOLUS VULGARIS L.) POD DERIVED CARBON DECORATED WITH FECO AS A BIFUNCTIONAL ELECTROCATALYST IN ZN-AIR BATTERY - ADIB ABDILLAH MAHBUB, MUHAMMAD
As the prime candidate of energy storage technologies, Zn-air battery has gained interest owing to its high theoretical energy density and utilization of abundant resources. Due to the sluggish kinetics reaction in the cathode of the Zn-air battery, a catalyst is required to boost the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). The stateof- the-art ORR and OER catalysts (i.e., platinum and iridium), are undesirable due to their scarcity, high-cost, and low stability. Considering this, the efficient bifunctional electrocatalyst with low-cost and easy production is necessary for pushing the research roadmap towards green and sustainable technologies. Biomass-derived carbon-based catalyst decorated with transition metal, and heteroatom doping is the alternative catalyst for the enhanced Zn-air battery performances. In this work, red bean pod waste as a carbon source decorated with FeCo and nitrogen doping is synthesized via simple pyrolysis. The carbon-based catalyst exhibits a high surface area of 625.5 m2 g-1, with an onset potential of 0.89 V for ORR activity, and an overpotential of 470 mV for OER activity. Introducing FeCo and nitrogen positively affect the bifunctional catalyst performance with an onset potential of 0.93 V and an overpotential of 360 mV. FeCo/N-C-Red Bean exhibits a peak power density of 116.2 mW cm- 2 and is stable for 70 hours and 210 cycles in practical Zn-air battery application. This work gives an insight into the utilization of agriculture wastes for value-added material and its application for Zn-air batteries.